Design of Interdisciplinary Operation Mechanism in Universities Considering Management Policy Constraints: A Multiagent Simulation Model - Shu Fan (Modelling and Simulation in Engineering)
Innovation is an important guarantee for maintaining national competitiveness and promoting social productivity, and it has a strong driving force for national and social development. At present, interdisciplinary research is widely used as a mechanism for innovation to solve complex problems, and universities are important subjects of innovation activities. Therefore, how to design the interdisciplinary operation mechanism in universities is of great significance to improving innovation productivity. This paper focuses on the design of interdisciplinary research management policies. By using a multiagent simulation model describing the university interdisciplinary research process, the useful management policies are determined by comparing the evolution results of the interdisciplinary research process under different management policy constraints. The simulation results show that (1) scientific research output and cooperation in interdisciplinary research of universities can be promoted by dynamic allocation policies, (2) interdisciplinary research performance can be increased by setting a proper number of research directions in universities, (3) the presence of teachers with high efficiency coefficient and high initial scientific research output will not negatively affect scientific research output and fairness of interdisciplinary research, and (4) high-level research output can be increased by setting proper rewards for high-level tasks in interdisciplinary research. The work of this paper can provide a basis for interdisciplinary research management policy design from a new theoretical perspective.